Application of the principle of retroactivity in ukrainian legislation for commitment of applicable offenses against property - Lototskyi M.; Dzundza L. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of the work is to study the extension of the principle of retroactivity to law-making and law-enforcement practice to the legal system in Ukrainian legislation. Methodology. The methodology includes a comprehensive analysis and generalization of the available scientific and theoretical material and the formulation of relevant conclusions. The following methods of scientific knowledge were used during the study: comparative law, logical-grammatical, system-structural, modeling. Results. During the study, it was recognized that in the legislation of Ukraine, in the process of creating and implementing legal norms, general principles of law are applied, which are guided by state authorities and local governments in their activities within the framework of their competence. When adopting new regulatory legal provisions or making changes to existing ones, general principles of law must be applied. The application of the principle of retroactivity of law allows individuals and legal entities to be confident in the legal assessment of their actions not only when they are committed, but also in the future. Scientific novelty. In the process of research, it was scientifically substantiated that the criminal procedural legislation of Ukraine as a whole complies with the Fundamental Law of Ukraine and the practice of the European Court of Human Rights during criminal proceedings when changing the punishment for committing criminal offenses.